1996
DOI: 10.1093/nar/24.11.1981
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors Sp1 and Oct-1 interact physically to regulate human U2 snRNA gene expression

Abstract: The expression of human small nuclear U2 RNA genes is controlled by the proximal sequence element (PSE), which determines the start site of transcription, and a distal sequence element (DSE). The DSE contains an octamer element and three Sp1 binding sites. The octamer, like the PSE, is essential for U2 transcription. The Sp1 sites contribute to full promoter activity by distance-dependent cooperative interactions with the transcription factors Sp1 and Oct-1. Here we show that purified recombinant Sp1 and Oct-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 39 publications
0
46
0
2
Order By: Relevance
“…This domain contains 52 glutamines interrupted mainly by histidines, resulting in a highly polar stretch suitable for interactions. Certainly, Q-rich domains are present in proteins with diverse roles in gene expression and serve as proteinprotein interaction and multimerisation modules (Pascal and Tjian 1991;Emili et al 1994;Stott et al 1995;Strom et al 1996). To test whether the Q-rich domain could confer translational repression, we deleted it from dUNR and fused it to hUNR.…”
Section: Discussionmentioning
confidence: 99%
“…This domain contains 52 glutamines interrupted mainly by histidines, resulting in a highly polar stretch suitable for interactions. Certainly, Q-rich domains are present in proteins with diverse roles in gene expression and serve as proteinprotein interaction and multimerisation modules (Pascal and Tjian 1991;Emili et al 1994;Stott et al 1995;Strom et al 1996). To test whether the Q-rich domain could confer translational repression, we deleted it from dUNR and fused it to hUNR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that these elements enhance DNA replication and have identified Sp1 sites as important components (39,40). Because Oct-1 and Sp1 can physically interact (41), it is possible that Oct-1 contributes to the Sp1-dependent stimulation. However, this model is unlikely to account for the striking requirement for Oct-1 at this stage of infection, because the IE elements have only a minor stimulatory effect on DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Q-rich domains have been shown to be involved in the interaction between Sp1 and different classes of nuclear proteins, such as TATA-binding protein associated factors (TAFs), which are components of the general transcription factor TFIID. [8][9][10][11][12] The interaction between Sp1 and TAF4 via each Q-rich domain is considered to recruit RNA polymerase II to the transcription initiation site and activate transcription.…”
Section: Introductionmentioning
confidence: 99%